European strategy for determining the level of competence in the field of digital technologies: a framework for digital competence for citizens (Educational Dimension, 2020)
The Digital Competence Framework for Citizens (DigComp 2.0: Digital Competence Framework for Citizens), presented by the European Commission in 2016 and modernized in 2017 (DigComp 2.1) is supplemented with examples of application in different European countries, is described. Today, the Digital Competence Framework for Citizens 2.0 and 2.1 is one of the latest modern European strategic documents developed by the European community of countries that create educational standards and educational technologies. The need to have digital competence as a teacher is today a personal, professional need and challenge in a rapidly evolving technology. It is important for modern educational reforms to meet this need through a system of professional development, taking into account the need for lifelong learning. Acquaintance with the achievements of the European community, with the Digital Competence Framework for Citizens will contribute to a holistic vision of this category and progress towards the formation of this important key human capacity. Descriptors of learning outcomes in the field of digital competence are described. Prospects for further research are identified, which are the use of the Digital Competence Framework for citizens in the field of educational policy and in practice in educational institutions.